A Communication System Design Use Voice Over Internet Protocol (VOIP) Based On Arduino Nano ESP32 At Medan Aviation Polytechnic - Ludfia Anggi Safitri Sinaga; Bela Firmantoyo; Darmeli Nasution (Sean Institute, 2024)
A good communication tool must convey information clearly and be well received by the recipient. Currently, communication between units at the Medan Aviation Polytechnic still uses the Public Switched Telephone Network (PSTN) telephone network. This communication system has disadvantages, such as high maintenance costs and dependence on cable instructors. Therefore, in this research, the author created an alternative VOIP transmission media design based on Arduino Nano dan ESP32 aimed at reducing maintenance costs and making it easy to integrate with the sophisticated and flexible technology of the PSTN. Arduino Nano dan ESP32 is used as the main controller connecting software and hardware. This type of design and development research aims to create a product and test it using functional methods to ensure this communication tool works well to convey information to the recipient. The test results show that this communication tool effectively conveys more accurate information from one unit to another. Thus, this Arduino nano dan ESP32-based communication tool can be a useful tool for providing information quickly, effectively, and efficiently.